Zinek a jeho sloučeniny - Štefka, Michal (Vysoké učení technické v Brně. Fakulta chemická, 2010)
Cílem bakalářské práce je příprava tří po sobě jdoucích sloučenin zinku. V teoretické části si práce všímá nejčastějších fyzikálních a chemických vlastností některých anorganických sloučenin tohoto prvku. Jsou to především ty sloučeniny, které jsou připraveny jako produkty nebo meziprodukty podle návodů uvedených v příloze této práce. V experimentální části je na základě poznatků ze samotné přípravy popsáno skutečné chování zinku oproti obecně uváděnému knižnímu a uvedeny postupy s nejvhodnějšími podmínkami přípravy jednotlivých sloučenin.

The aim of the degree work is the preparation of three consecutive zinc compounds. The theoretical part of the work deals with the most common physical properties of some inorganic compounds of this element. These are especially those compounds that are prepared as intermediates or products in accordance with the instructions set out in the Annex to this degree work. In the experimental part is on the basis of that training described the actual behavior of zinc compared to that provided by general behavior contained in the books and there are presented procedures best saited to the conditions of preparation of individua compounds.
Zinc and its compounds
Keywords: Anorganická chemie; zinek; sloučeniny zinku; oxid zinečnatý; síran zinečnatý; uhličitan zinečnatý; heptahydrát síranu zinečnatého; Inorganic chemistry; zinc; zinc compounds; zinc oxide; zinc sulphate; zinc carbonate; heptahydrate of zinc sulphate